Analisis Penataan Kawasan Ruang Terbuka Hijau (RTH) Di Kota Pangkajene Kabupaten Sidenreng Rappang - Reza Ahmad Hidayat (Departemen Ilmu Pemerintahan Fisip Unhas, 2017)
This study aims to determine the arrangement of green open spaces in the City Pangkajene Sidenreng Rappang Regency and the factors that influence it. To achieve these objectives, used qualitative research methods by parsing data descriptively. Data collection technique is done by observation, interview, and document and archive by using qualitative descriptive analysis technique. The result of the research shows: Firstly, in the implementation of the spatial plan policy related to Green Open Space (RTH) in Pangkajene City until now, it can be seen that there is still nonconformity between the provision of Green Open Space (RTH) of Urban Area. Second, the management of green space is done regularly and continuously involving various agencies and communities, and considering there are still some complaints from the public regarding the cleanliness and beauty of the green space. Supporting factors are Regional Regulations that support the arrangement of green open spaces, as for the factors that hamper air pollution and increasing global warming and lack of public awareness.